Jejueo The Language of Korea's Jeju Island - Yang, Changyong (University of Hawaii Press, 2019)
Jeju Island, located about 30 miles southwest of the Korean mainland, is famous for its natural beauty, dolhaleubang ("stone grandfather") statues, haenyeo ("sea women") divers-and its language, which has only recently been recognized as distinct from Korean. This finding-still considered controversial-undermines the centuries-old belief that Korea has a single language within its borders and opens the door to an entirely new perspective on linguistic diversity in East Asia.Jejueo: The Language of Korea's Jeju Island offers both an introduction to the language and the foundation for a wave of new research on its many unique features. Through its comprehensive approach, the book helps establish the importance of Jejueo to the cultural and linguistic heritage of not only Jeju Island, but also the entire Korean peninsula. After a brief introductory chapter on the history of the island and its culture, the authors work their way through the language step by step, examining its sounds, part-of-speech system, and rich inventory of suffixes for both nouns and verbs, to which several chapters are devoted. Carefully written to minimize technical language and supplemented with hundreds of examples, the work is intended to be accessible to scholars working in all fields of Korean studies.Jejueo tells the story of a language that has been under wraps for far too long and is now in peril. After centuries of use as the first language of the island, only a few thousand elderly fluent speakers remain, leading UNESCO to classify Jejueo as "critically endangered" in 2010. As the first full-length treatment of Jejueo in English, this book marks a milestone in Korean studies and is sure to trigger extensive discussion of the language and its place in Korean society.